1900 N.Y. Laws 1174, ch. 494, § 1. - (:unkn) unknown (General Publisher, 1900)
A person who makes or keeps gunpowder, nitro-glycerine, or any other explosive or combustible material, within a city or village, or carries such materials through the streets thereof, in a quantity or manner prohibited by law or by ordinance of the city or village, is guilty of a misdemeanor. A person who manufactures gunpowder, dynamite, nitro-glycerine, liquid or compressed air or gases, except acetylene gas and other gases used for illuminating purposes, naptha, gasoline, benzine [sic] or any explosive articles or compounds or manufactures ammunition, fireworks or other articles of which such substance are component parts in a cellar, room or apartment of a tenement or dwelling house or any building occupied in whole or in party by persons or families for living purposes, is guilty of a misdemeanor
--
Keywords: TRANSFER; MANUFACTURE & STORAGE OF GUNPOWDER